Periodontitis and pulmonary repercussions: Is the casual relationship between them well clarified in the literature? (Research, Society and Development, 2022)
Introduction: The oral cavity is a potential reservoir of respiratory pathogens. The mechanisms of infection that can be cited are the aspiration of bacteria that normally reside in the oropharynx, the colonization of dental plaque by respiratory pathogens followed by aspiration, and the ease of colonization of periodontal pathogens in the upper airway, thus providing a link between periodontitis and respiratory/pulmonary conditions also of an inflammatory nature. However, the causal relationship between periodontitis and the development of pulmonary disorders is not well understood. This research aims to verify the advances in the discussions of the relationship between periodontitis and pulmonary diseases. Metodology: This is an sistematic literature review study. The guiding question of the research was elaborated using the strategy of the acronym PICO. Searches for eligible studies were carried out from January 31, 2022 to February 16, 2022, in the databases: PubMed and BVS Library, using elements from the PICO acronym to obtain specific and controlled descriptors, available in Descriptors in Health Sciences/Medical Subject Headings (DeCS/MeSH): periodontitis, inflammation, lung diseases, which were combined during the search by the boolean AND operator. Case reports, clinical study, clinical trial, observational study, randomized controlled trial, available in English, Chinese and Portuguese, were selected, attributing a time cut of 12 years (2010-2022). Inclusion criteria were: original and review articles whose main subject was related to periodontitis and its relationship with pulmonary disorders. The following were excluded: duplicate works, incomplete works, studies that omitted the sample size, study protocols, articles outside the time frame of the research, works without relevant results or out of context, articles whose research addressed studies in animals and articles with conflict of interest. interests among the authors. 69 articles were identified in the databases defined for the search. After the process of selection and analysis of the works found, 21 articles were selected for review. Results and discussion: The results are organized according to the presentation of the sample variables (sample size, characteristics of the participants regarding: age, sex, presence of periodontitis, presence of COPD, presence of periodontitis concomitant with COPD), research design, type of intervention (description of procedures in relation to treatment, assessment of periodontal status and respiratory functions), type of control for the treatment group, and description of the main outcomes (changes in quality of life, oral hygiene status and functioning of respiratory functions evaluated in the participants, before and after the intervention). Conclusion: The relationship between periodontitis and lung conditions is well elucidated in the literature, especially in patients who have both conditions (periodontitis and lung disorders). However, it can also be observed that there is no clear and substantial evidence that explains the causal mechanisms between them. This review alludes and points to better clarifications in this field.